TRANSINTERNALISASI BUDAYA PENDIDIKAN ISLAM: MEMBANGUN NILAI ETIKA SOSIAL DALAM PENGEMBANGAN MASYARAKAT - Imam Mawardi (State Institute of Islamic Studies (IAIN) Palu, 2011)
Abstract: Islamic education is a conservationist and connector for socio-ethical values of society. Therefore, the paradigm which should be established is how to adapt Islamic education with social changes based on the modernity with moral values as outlined in the teachings of Islam. With social ethics, Islamic education can became a bridge for the global issues in all aspects of community culture, beginning from family to the larger and more complicated communities. Hence. the system of Islamic education which should be actualized is that related to interdisciplinary, multi-disciplinary and transdisciplinary subject with the policy of mutual binding between the compliance of socio-religio cultural values and the needs of the market.Kata Kunci: transinternalisasi, pendidikan Islam, etika sosial, masyarakat